2019
DOI: 10.1021/acs.orglett.9b02058
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Aziridines via Catalytic Asymmetric Ring-Opening Reaction with Mercaptobenzothiazoles

Abstract: A highly efficient kinetic resolution of racemic 2-acyl-3-aryl-N-tosylaziridines is achieved through a chiral Lewis acid promoted ring-opening reaction with 2-mercaptobenzothiazoles as the nucleophiles. The chiral N,N′-dioxide–lanthanum complex as catalyst and the 2-mercaptobenzothiazoles as active sulfur nucleophiles are the keys to the success of the reaction. A variety of enantioenriched β-amino thioethers and aziridines are obtained in good yields with good ee values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…4d,e In 2019, Lin, Feng, and co-workers realized the first kinetic resolution of trans-2,3-disubstituted aziridines via nucleophilic ring opening with mercaptobenzothiazoles by using La(OTf) 3 and Feng's chiral N,N′-dioxide ligands (Scheme 10). 21 The reaction worked well with a range of racemic chalcone-derived 2-aroyl-3-arylaziridines and exclusive regioselectivity and moderate-to-high selectivity factors were obtained. While a series of mercaptobenzothiazoles, including 4,5-dihydrothiazole-2-thiol without a phenyl ring, participated in the reaction well, 4-methylthiophenol (48) and 2-thionaphthol (47) provided poor yields and cyclohexanethiol (49) did not undergo the reaction under these conditions.…”
Section: Short Review Syn Thesismentioning
confidence: 87%
“…4d,e In 2019, Lin, Feng, and co-workers realized the first kinetic resolution of trans-2,3-disubstituted aziridines via nucleophilic ring opening with mercaptobenzothiazoles by using La(OTf) 3 and Feng's chiral N,N′-dioxide ligands (Scheme 10). 21 The reaction worked well with a range of racemic chalcone-derived 2-aroyl-3-arylaziridines and exclusive regioselectivity and moderate-to-high selectivity factors were obtained. While a series of mercaptobenzothiazoles, including 4,5-dihydrothiazole-2-thiol without a phenyl ring, participated in the reaction well, 4-methylthiophenol (48) and 2-thionaphthol (47) provided poor yields and cyclohexanethiol (49) did not undergo the reaction under these conditions.…”
Section: Short Review Syn Thesismentioning
confidence: 87%
“…Over the past two decades, chiral rare-earth metal complexes have emerged as potent catalysts in the realm of asymmetric synthesis . Among these, chiral lanthanum­(III) complexes have gathered considerable attention. Due to the substantial ionic radius and high coordination number of lanthanum­(III), , the hapto number and steric hindrance of the ligands displayed a dramatic effect on coordination modes and coordination numbers of lanthanum­(III) complexes. Till now, the selection of chiral ligands compatible with it has remained limited.…”
mentioning
confidence: 99%
“…The catalytically active species in this context have been identified as lanthanum­(III)/three alkali metals (M 3 )/tris­(BINOLate) complexes ( LaMB ) (Scheme a). Feng and colleagues utilized N , N ′-dioxide , as a tetradentate oxygen ligand to synthesize La­(III)/ N , N ′-dioxide complexes, which found application in several asymmetric reactions (Scheme a) . Although crystals of La­(III)/( L 3 -RaMe 2 ) 2 was obtained, the experiment studies suggested that La­(III)/ L 3 -RaMe 2 may be the catalytically active species for asymmetric ring-opening reaction of aziridines with mercaptobenzothiazoles .…”
mentioning
confidence: 99%
“…The aziridine functionality is one of the most valuable three membered ring systems in modern synthetic chemistry, and catalytic asymmetric nucleophilic ring opening reactions of ethylenimine units have emerged as a powerful chemical tool for the synthesis of various nitrogen-containing biologically active compounds . In this context, remarkable progress has been achieved in desymmetric ring opening reactions of meso -aziridines and kinetic resolution of racemic unfunctionalized terminal or internal aziridines with various nucleophiles. For instance, the Chai group realized the kinetic resolution of 2-aryl- N -tosylaziridines and the asymmetric desymmetrization of meso - N -tosylaziridines via Ag catalyzed ring openings with amine nucleophiles in 2017.…”
mentioning
confidence: 99%